2022
DOI: 10.1002/adom.202201055
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitive Ratiometric Thermometry and Manometry Based on Dual‐Emitting Centers in Eu2+/Sm2+‐Doped Strontium Tetraborate Phosphors

Abstract: of high sensitivity has become a continuously more important and challenging task, as increasing demand for both industrial development and various scientific research purposes. However, the conventional thermometers based on the expansion of liquids or metals, such as mercurial thermometer, thermocouples or pyrometers suffer from several shortages, such as: limited spatial resolution (inability to detect the temperature of an object with the scale below 10 µm), often necessity of physical contact, low sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Since the emission band of the Cr 3+ ions of Al 2 O 3 : Cr 3+ spectrally overlaps with the emission band of the analyzed SrGdAlO 4 : Mn 4+ , the spectral shift of the SrB 4 O 7 : Sm 2+ 5 D 0 → 7 F 0 emission line was used as a pressure indicator in the DAC. 30 The sample was placed in a ≈140 μm size hole drilled in a 250 μm thick stainless steel gasket. The methanol–ethanol solution (4 : 1 ratio) was used as a pressure transmission medium.…”
Section: Methodsmentioning
confidence: 99%
“…Since the emission band of the Cr 3+ ions of Al 2 O 3 : Cr 3+ spectrally overlaps with the emission band of the analyzed SrGdAlO 4 : Mn 4+ , the spectral shift of the SrB 4 O 7 : Sm 2+ 5 D 0 → 7 F 0 emission line was used as a pressure indicator in the DAC. 30 The sample was placed in a ≈140 μm size hole drilled in a 250 μm thick stainless steel gasket. The methanol–ethanol solution (4 : 1 ratio) was used as a pressure transmission medium.…”
Section: Methodsmentioning
confidence: 99%
“…The lowest obtained eigenvalue corresponds to the energy of the 2 E emitting state for given d and g. Finally, calculating 2 E -4 A 2 requires subtracting the energy of the ground state 4 A 2 (À15B); see eqn (17).…”
Section: Crystal Field Parameter Calculationsmentioning
confidence: 99%
“…So far such phosphors have not been found; however, there have been several reports of luminescent pressure sensors for the GPa pressure ranges, encountered in high-pressure experimental settings. [15][16][17][18] Secondly, high pressure spectroscopy can be viewed as a powerful analytical tool that uncovers additional information about the spectroscopic properties of phosphors by examining pressure shifts in optical spectra, electronic level crossings or changes in the luminescence decay. 2,19 This is especially attractive, since there is a correspondence between the properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional contacted thermometers, a lot of attention has been attracted by luminescence thermometers, which utilize temperature-associated fluorescence characteristics, such as fluorescence intensity ratio (FIR), band position, decay time, full width at half-maximum of emission band, etc., of luminescent materials because of their advantages of rapid response, high accuracy/resolution, and contactless characteristic. , Particularly, by adopting the FIR technique, optical thermometry is extensively adopted, in which the temperature-related emission intensities of thermally coupled levels (TCLs) of rare-earth ions are investigated. , Fu et al revealed that the thermometric properties of rare-earth ions, which were based on their TCLs, can be adjusted by controlling the excitation wavelength and utilizing tridoping engineering. , However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity ( S r ) triggered by the small energy band gap of TCLs (200 ≤ Δ E ≤ 2000 cm –1 ). , For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ /Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ /Eu 3+ , with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing. Thereby, the utilization of the temperature-dependent FIR value of non-TCLs is a facile strategy to manipulate the thermometric behaviors of luminescent materials.…”
Section: Introductionmentioning
confidence: 99%